STRATEGI PEMERINTAH DAERAH TERHADAP KUNJUNGAN WISATA CANDI MUARA TAKUS KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR SELAMA COVID-19 - Lisa Nurmaya; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Muara Takus Temple is one of the leading tourist attractions in Riau Province in Kampar Regency, because it is the only historical heritage site in the form of a temple in Riau. The purpose of this research is to find out the local government's strategy for tourist visits to the Muara Takus temple, XIII Koto Kampar District, Kampar Regency during Covid-19. Then to find out the inhibiting factors of the local government's strategy for tourist visits to the Muara Takus temple, XIII Koto Kampar District, Kampar Regency during Covid-19. The theory used in this research is strategic management theory according to Fred R. David. This type of research used is qualitative. While the research approach used is descriptive. Data were collected by the authors using interview and documentation techniques. The data used are primary data obtained from research informants and further supported by secondary data obtained from various government agencies related to this research. The results showed that there were three strategies in developing the Muara Takus Temple tourist attraction, namely forming a strategy for developing the Muara Takus Temple tourist object, implementing the Muara Takus Temple tourist attraction development strategy, and evaluating the development strategy for the development of the Muara Takus Temple tourist attraction. The inhibiting factors for the Tourism and Culture Office's strategy are the lack of public participation and awareness and budget constraints in developing the Muara Takus Temple tourist object, the lack of supporting facilities and infrastructure, and the lack of interest from investors to invest. Keywords: Strategy, Tourism Object, Muara Takus Temple